The dynamics of government attention on health policies in Brazil: balance and punctuation in the first decades after re-democratization (1986-2003) - Brasil, Felipe [UNESP]; Capella, Ana Claudia [UNESP] (Univ Sao Paulo, Fac Saude Publica, 2019)
This paper aims to map and analyze the attention of some actors and institutions on health policies in Brazil between 1986 and 2003. This model of research on the government agenda is known under the term of policy dynamics and analyzes the process of changing public policies by the entering and exiting of topics in the priorities of policymakers. More than 10,000 data from five different sources (messages to the Congress, legislative output, approved annual budget, Federal Constitution of 1988 and minutes of national health conferences) were selected and analyzed in order to identify the attention of these actors to specific topics on health policy. The frequency analyses, both on longitudinal and cross-sectional perspective, are based on a large set of data that reflect the government's attention during the first decades after the re-democratization in Brazil and allow for the observation and maintenance of changes in health policies. As a result, it was possible to identify permanence in the government attention on health policies throughout the analyzed period, showing a permanent and constant degree of attention to this sectoral policy. From the dynamics point of view, maintenance, discrete and incremental adjustments in health policy were identified most of the time, but also moments of great transformations were punctuated during the period.
Keywords: Public Policy; Policy Agenda; Health Policy; Policy Dynamics